Tomato fruits: a good target for iodine biofortification - Kiferle, Claudia; Gonzali, Silvia; Holwerda, Harmen T.; Real Ibaceta, Rodrigo; Perata, Pierdomenico (Frontiers in Plant Science, 2013)
Iodine is a trace element that is fundamental for human health: its deficiency affects about two billion people worldwide. Fruits and vegetables are usually poor sources of iodine; however plants can accumulate iodine if it is either present or exogenously administered to the soil. The biofortification of crops with iodine has therefore been proposed as a strategy for improving human nutrition. A greenhouse pot experiment was carried out to evaluate the possibility of biofortifying tomato fruits with iodine. Increasing concentrations of iodine supplied as KI or KIO3 were administered to plants as root treatments and the iodine accumulation in fruits was measured. The influences of the soil organic matter content or the nitrate level in the nutritive solution were analyzed. Finally, yield and qualitative properties of the biofortified tomatoes were considered, as well as the possible influence of fruit storage and processing on the iodine content. Results showed that the use of both the iodized salts induced a significant increase in the fruit’s iodine content in doses that did not affect plant growth and development. The final levels ranged from a few mg up to 10 mg iodine kg-1 fruit fresh weight and are more than adequate for a biofortification program, since 150 µg iodine per day is the recommended dietary allowance for adults. In general, the iodine treatments scarcely affected fruit appearance and quality, even with the highest concentrations applied. In contrast, the use of KI in plants fertilized with low doses of nitrate induced moderate phytotoxicity symptoms. Organic matter-rich soils improved the plant’s health and production, with only mild reductions in iodine stored in the fruits. Finally, a short period of storage at room temperature or a 30-minute boiling treatment did not reduce the iodine content in the fruits, if the peel was maintained. All these results suggest that tomato is a particularly suitable crop for iodine biofortification programs.